Evaluation of Daily Traffic Activities At Four-Legged Intersection Of Cimencrang, Al Jabbar Mosque Area, Using PKJI 2023 - Lazuardi, Rahmat; Septiawati, Vera; Septiani, Anis (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2024)
This study evaluates the impact of daily traffic activity at the four-legged intersection at the Cimencrang railway crossing, in the Al Jabbar Mosque area, using the Indonesian Road Capacity Guidelines (PKJI) 2023. The aim of this study is to assess the traffic performance affecting the efficiency of at-grade road and railway crossings in the area. This evaluation is essential to understand the traffic dynamics in the area, which will help the government in designing traffic and transportation management methods to reduce future congestion. Traffic data was collected through direct surveys during peak hours on weekdays, covering vehicle volume, vehicle types, and the geometric dimensions of the roads at the intersection. The evaluation results indicate that the intersection’s Volume to Capacity Ratio (VCR) at the study site is 0.74. The findings also suggest that this four-legged intersection frequently experiences critical conditions, with Levels of Service (LOS) ranging from C to E during busy hours. The study recommends improving traffic management and infrastructure to enhance performance and traffic conditions, as well as road user safety in this area. It is hoped that these findings can serve as a foundation for local government in planning more effective traffic policies in the area, and provide insights into the processes and procedures of traffic evaluation at four-legged intersections.